Life-course trajectories of risk-taking propensity: A coordinated analysis of longitudinal studies - Liu, Yunrui; Bagaini, Alexandra; Son, Gayoung; Kapoor, Madlaina; Mata, Rui (My University, 2022)
How does risk preference change across the life span? We address this question by conducting a coordinated analysis to obtain the first meta-analytic estimates of adult longitudinal age differences in risk-taking propensity in different domains
PsyArXiv Preprints
Keywords: Health and wellbeing